Foliar nutrient resorption stoichiometry and microbial phosphatase catalytic efficiency together alleviate the relative phosphorus limitation in forest ecosystems - Peng, Ziyang (The New phytologist, 2023)
© 2023 The Authors New Phytologist © 2023 New Phytologist Foundation.